Ischemic stroke of the left claustrum in a 55-year-old female: a case report. Issue 1 (1st January 2018) - Maximov, Georgi K.; Hinova-Palova, Dimka V.; Iliev, Alexandar A.; Kotov, Georgi N.; Kirkov, Vidin K.; Landzhov, Boycho V.; Maksimov, Konstantin G.
ABSTRACT: Background : The claustrum is a brain structure found in both hemispheres beneath the inner surface of the neocortex in the region of the insula and is bordered by the external and extreme capsule. Generally, it is divided into a dorsal part (claustrum proper or insular claustrum) and ventral part (endopiriform nucleus). The claustrum possesses complex reciprocal connections with the cortex, striatum, dorsal thalamic nuclei and hippocampus. Reports of patients with unilateral lesion of the claustrum are few in number. Herein, we present a case report of an ischemic stroke restricted to the left claustrum in a 55-year-old female Case Report : The patient presented with intense feeling of dizziness, ataxic gait, sensation of 'vacuity' in the head, decreased hearing and abnormal gustatory sensations. The neurological examination revealed a mixed horizontal and rotary nystagmus to the right side. Brain CT upon admission was assessed as normal without pathological findings. MRI was performed and showed an ischemic stroke restricted to the left claustrum with no other lesions. Following 4 weeks of therapy the patient recovered fully and duplex sonography showed preserved circulation in the affected areas. Conclusion : The present case report underlines the complexity of clinical symptomatology of the claustrum.